PHONOLOGICAL LEVEL IN ALLAMA IQBALâ€™S POEM â€œTHE BIRDâ€™S COMPLAINTâ€: A STYLISTIC ANALYSIS - Syahputra, Fikry Prastya; Sari, Indah Permata; Sinar, Tengku Silvana (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2018)
Allama Iqbal is one of some poet who declares himself as a fighter toward social arouse and problem in his country. Through his poet, he created a spirit to restrain against injustice in his country. This study aimed to analyze one of Allama Iqbal poet in the term of a phonological level. The theory used is a stylistic approach. It found that the poet used alliteration, assonance, consonance, rhyme scheme, and onomatopoeia as the phonological devices in stylistics. The phonological devices in the poem are used to create a good rhyme or musical in order to make the poem more beautiful when it is read loudly. Consonance is the most phonological devices applied in the poem, and the sound /n/ is the most consonance sound found in the poem. The assonance is in the second place with the sound /É™/ and /Éª/ as the most assonance sound used in the poem. The alliteration found is sound /n/ and /s/ as the most alliteration sound found in the poem. In the rhyme scheme, the poem almost has the monotonous rhyme because almost all of the stanzas have the rhyme â€˜aa,' but it also contains the rhyme â€˜ab.'